Farmer-Led integrated watershed management : (Participatory Watershed Management Training in Asia and Farmer-Centred Agricultural Resource Management Programmes, FAO (UN), 1997)
The book attempts to present, through eight modules, a scenario for facilitating upland, integrated watershed development led by the farmers and other land users. These eight modules deal with a range of issues from a mountain perspective: processes of development; socio-cultural factors; and gender concerns. The aim of this resource book is to emphasise integrated upland watershed development processes for facilitating farmers' ownership of the programmes. The manual describes the changing scenarios of the livelihood options being pursued by mountain farmers to manage common property resources effectively through a community approach to development in the Asian region